Analisis Hubungan Kausalitas Pertumbuhan Ekonomi, Jumlah Penduduk Miskin Dan Ekspor Industri Di Provinsi Jawa Barat - Mubarak, Alfan; Samsuddin, M. Afdal (CV. SINAR HOWUHOWU, 2025)
This study aims to analyze the causal relationship between economic growth, poverty, and industrial exports in West Java Province using the Vector Error Correction Model (VECM) approach. The data used are annual secondary data from 2014 to 2023, which were interpolated into monthly data. The research begins with a stationarity test, followed by the Johansen cointegration test, VECM estimation, as well as Granger causality, impulse response function (IRF), and variance decomposition (VD) analyses. The results indicate the existence of a long-term relationship among the variables, making the VECM model suitable for use. The Granger test shows that industrial exports significantly affect economic growth but do not directly influence poverty reduction. The IRF results reveal that economic growth and poverty are more responsive to their own internal shocks, while cross-variable effects are present but relatively weak. The variance decomposition analysis supports this finding, with most fluctuations explained by internal shocks, except for economic growth, which is also influenced by export contributions. These findings emphasize the importance of optimizing the industrial export sector as a driver of sustainable economic growth, alongside inclusive policies to ensure that such growth translates into meaningful poverty reduction in West Java.